Mindfulness, Perceived Partner Responsiveness, and Relational Conflict Among Emerging Adult Couples - Lachance-Grzela, Mylène; Ross-Plourde, Mylène; Vautour, Manon; Larocque, Marilou; Duguay, Amanda (Canadian Journal of Counselling and Psychotherapy, 2020)
The current study examines the ways in which perceived partner responsiveness can explain the link between trait mindfulness and conflicts among emerging adult couples. Members of a total of 127 mixed-gender couples completed a series of questionnaires. Mediation analyses revealed that, for men, mindfulness was associated with fewer and less intense relational conflicts and that this association was explained partially by perceived partner responsiveness. For women, partner responsiveness was also associated negatively with reported conflicts, but mindfulness was not related directly or indirectly to relational conflicts. Our results suggest that mindfulness and responsiveness can contribute to the understanding of relational conflicts among emerging adult mixed-gender couples. Implications for counselling and psychotherapy are discussed.